Myelinoclastic diffuse sclerosis (Schilder’s disease) is immunologically distinct from multiple sclerosis: results from retrospective analysis of 92 lumbar punctures - Jarius, Sven; Haas, Jürgen; Wildemann, Brigitte (Journal of neuroinflammation, 2019)
Myelinoclastic diffuse sclerosis (MDS; also termed Schilder’s disease) is a rare inflammatory demyelinating disorder of the central nervous system characterised by demyelination of vast areas of the white matter. It is unclear whether MDS is a variant of multiple sclerosis (MS) or a disease entity in its own right.